Changing public policy on expenditure in Namibia after independence and its impact on healthcare and education. (12th March 2021) - De, Utpal Kumar; Shafuda, Christopher P.P.
In this paper, we examined whether changes in fiscal measures through increasing government expenditure on education and healthcare services adopted after independence has made significant impact on the welfare of the Namibian people. Time series data from Ministry of Finance, Ministry of Education of Government of Namibia, Namibia Statistics Agency and World Bank during the period between 1980 and 2015 has been used for the purpose of analysis. A comparison of growth in such expenditures, GDP and other human development indicators has been made between the pre- and post-independence periods. Finally, impacts of changes in healthcare and education expenditure on reduction in mortality, increase in life expectancy at birth, rising literacy and growth of people acquiring higher/technical education, etc. have been examined by using regression analysis. It is revealed that the Namibian people are better off now as compared to the pre-independence era. However, policy changes adopted at the time of independence has not been highly successful in transforming life of the Namibian people as expected. There are still a lot of scopes for the improvement of fiscal management in the country.